2019
DOI: 10.29354/diag/110241
|View full text |Cite
|
Sign up to set email alerts
|

A review of methods for excitation force reconstruction

Abstract: In many mechanical systems research scenarios, including in particular control and monitoring of mechanical devices, reconstruction of external loads acting on a system is a matter of great importance. The paper provides taxonomy and review of available dynamic load identification methods in cases when a direct load applied to the structure is required to be reconstructed. Methods based on frequency and time domains as well as those relying on statistical and soft computing approaches are described. The author… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…Force identification methods can be classified according to the domain in which they operate, and the nature of the algorithm used [ 1 ]. The first classification distinguishes two categories: time domain and frequency domain identification methods.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Force identification methods can be classified according to the domain in which they operate, and the nature of the algorithm used [ 1 ]. The first classification distinguishes two categories: time domain and frequency domain identification methods.…”
Section: Introductionmentioning
confidence: 99%
“…The second classification distinguishes three groups: deterministic, statistical, and artificial intelligence-based methods. Within these three groups, there are many effective force identification algorithms, an overview of which can be found in [ 1 , 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Comprehensive review of the different OMA algorithms can be found in the article by Zahid et al [25]. The attempt to create an automated OMA together with thorough analysis of the influence of different selection of an estimation parameters can be found in paper by Rainieri and Fabbrocino [26]. OMA has many advantages such as the use of actual excitation levels and thus the study of the machine's dynamic properties at the operating point has been conducted.…”
Section: Introductionmentioning
confidence: 99%
“…Increasing the number of sensors recording responses improves the numerical conditioning of the method. One of the most recent reviews on the topic of excitation forces identification can be found in [ 2 ]. Other articles comparing methods for identifying forces are the works by Sanchez and Benarova [ 3 ] and Uhl [ 4 ].…”
Section: Introductionmentioning
confidence: 99%